2015
DOI: 10.1136/bmj.h5203
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate for attention-deficit/hyperactivity disorder in children and adolescents: Cochrane systematic review with meta-analyses and trial sequential analyses of randomised clinical trials

Abstract: Study queStionIs methylphenidate beneficial or harmful for the treatment of attention-deficit/hyperactivity disorder (ADHD) in children and adolescents? MethodSElectronic databases were searched up to February 2015 for parallel and crossover randomised clinical trials comparing methylphenidate with placebo or no intervention in children and adolescents with ADHD. Meta-analyses and trial sequential analyses (TSA) were conducted. Quality was assessed using GRADE. Teachers, parents, and observers rated ADHD sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 58 publications
12
124
2
4
Order By: Relevance
“…Results from our meta-regression suggest that ER formulations are equally effective as IR formulations in improving academic performance, which is in line with findings from individual studies comparing ER and IR formulations [52,62,63]. We found no effects of titration method (clinical titration prior to the trial or fixed dosages) which is also in line with findings from [61]. Possibly, to optimize the effects of MPH on academic outcome, titration should be based on academic outcomes instead of on symptom improvements.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results from our meta-regression suggest that ER formulations are equally effective as IR formulations in improving academic performance, which is in line with findings from individual studies comparing ER and IR formulations [52,62,63]. We found no effects of titration method (clinical titration prior to the trial or fixed dosages) which is also in line with findings from [61]. Possibly, to optimize the effects of MPH on academic outcome, titration should be based on academic outcomes instead of on symptom improvements.…”
Section: Discussionsupporting
confidence: 89%
“…Demographic and disorder-related variables included in our analysis (age, gender, ADHD subtype and ADHD severity) did not moderate MPH efficacy on math performance either. The absence of a moderating effect of age and comorbid disorders is in line with the results of a recent meta-analysis on behavioral improvements with MPH [61]. In the meta-analysis by Storebø and colleagues, some evidence was found for a moderating effect of ADHD subtype and behavioral improvements, with highest MPH efficacy for the inattentive subtype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Reviews of pharmacotherapy studies note the inadequate reporting of drug trial methodology, publication bias, limited reliability of results, inadequate data regarding adverse events, and lack of evidence of long term benefit (e.g. Storebø et al, 2015). The most commonly cited reference in support of using stimulant medication is the American multi-modal treatment of ADHD (MTA) study, which concluded, in a 14-month randomized controlled trial, that patients receiving medication had better outcomes compared to those who did not (MTA Cooperative Group, 1999).…”
Section: Does the Concept Of Adhd Help Improve Clinical Outcomes?mentioning
confidence: 99%
“…B. eine Sonderschule), können Medikamente indiziert sein (Psychostimulanzien und Atomoxetin, weitere Informationen in den Leitlinien [18,29]). Die Wirksamkeit von ADHS-Medikamenten ist wissenschaftlich belegt (SMD 0,61-0,87 [26]), allerdings werden die Qualität und der methodische Standard der Studien als gering bewertet, und es fehlen methodisch verlässliche Langzeituntersuchungen [26]. Voraussetzungen für eine medikamentöse Therapie sind ausreichende ärztliche Erfahrung, regelmäßige Verlaufskontrollen und eine Weiterführung der bereits eingeleiteten, nichtmedikamentösen Maßnahmen.…”
Section: Medikamenteunclassified